Gambaran Faktor Resiko Kejadian HIV/AIDS Pada Ibu Rumah Tangga Di Kabupaten Madiun - Mochamad Putro Joko Wandiro; Avicena Sakufa Marsanti; Retno Widiarini (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2021)
ABSTRACTBackground: Acquired Immune Deficiency Syndrome (AIDS) was symptom of a disease that arises due to a viral illness. The number of HIV/AIDS cases in Madiun District in 2016 estimated 33 cases, in 2017 there were 91 cases and in 2018 there were 125 cases. This study aims to describe the factors that influence the incidence of HIV/AIDS in housewives.Method: This type of research is descriptive. The population in the study were all housewives who experienced HIV/AIDS in Madiun Regency as many as 172 people.Results: The results showed that IRT was in the age range of 26-35 years (26.7%), SMA/SMK (76.2%), and had a type of occupation as IRT (99.4%).Conclusion: Based on the results of this study, it is recommended that IRTs be more concerned about their health by taking HIV/AIDS prevention.Suggestion: Health officers are expected to determine strategic steps and improve health services to the community, as well as provide information on the dangers and impacts of HIV/AIDS.Keywords: HIV/AIDS, Housewife, Age, Education, Occupation